Coal slurry pressure gasification is jacket cooling formula process burner for stove - PAN YONG; ZHANG TAO; DAI WUJUN; BAO WEINA; TANG GUANGJUN; LI YAO; QIN BO; XING TAO; ZHAO QI; SONG CHENGKAI; XU GUANGYU (2017)
The utility model discloses a coal slurry pressure gasification is jacket cooling formula process burner for stove, including the nozzle body, be located nozzle body upper end the gas access, be located the shower nozzle subassembly of nozzle lower extreme and encircle the cooling water jacket in the nozzle body outside, the utility model discloses a jacket cooling can increase the flow area of cooling water, improves heat exchange efficiency, provides better cooling and protection to the nozzle, optimize each passageway annulus of nozzle inside, can adapt to the needs of different coals and reach better atomization effect, improve efficiency of carbon con version, high temperature resistant, corrosion resistant high strength wear -resistant material is adopted, process burner's life can be prolonged. 本实用新型公开种水煤浆加压气化炉用夹套冷却式工艺烧嘴，包括烧嘴本体、位于烧嘴本体上端的气体入口、位于烧嘴下端的喷头组件以及环绕在烧嘴本体外侧的冷却水夹套，本实用新型采用夹套冷却，可以增大冷却水的流通面积，提高换热效率，对烧嘴提供更好的冷却保护；对烧嘴内部各通道环隙进行优化，可以适应不同煤种的需要以及达到更好的雾化效果，提高碳转化率；采用耐高温、耐腐蚀的高强度耐磨材料，可以延长工艺烧嘴的使用寿命。